Development of Weebly-Based Digital Learning Media for Vernier Caliper Material for Class XI Automotive Engineering - Kurniawan Fitri Nugraha; Suhendar Suhendar; Moh Fawaid; Khoirul Munir (Universitas Sultan Ageng Tirtayasa, 2026)
This research was conducted because the problems faced by students regarding vernier calipers in schools have become very complex. The minimal use of technology-based learning media, the lack of infrastructure, and the lack of student interest in learning vernier calipers are things that need to be considered. Therefore, teachers must combine digital learning media and relevant materials that can be used for learning development. The purpose of this study was to determine the development process, the level of validity, and the level of practicality of Weebly-based digital learning media with vernier caliper learning materials. The research method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were students of Automotive Engineering 2, SMKN 2 Tangerang and productive teachers of Automotive Engineering. The results obtained from this study fall into the